IGARSS 2000. IEEE 2000 International Geoscience and Remote Sensing Symposium. Taking the Pulse of the Planet: The Role of Remot
DOI: 10.1109/igarss.2000.860505
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of landslide susceptibility analysis techniques using geographic information system (GIS)

Abstract: The purpose of this study is to develop landslide susceptibility analysis techniques using Geographic information system (GIS) and apply the newly developed techniques for assessment of landslide susceptibility to two study areas of Yongin and Janghung, Korea Landslide locations detected from interpretation of aerial photo and field survey, and topographic, soil, forest, and geological maps of the study area, Yongin, were collected. The data on the locations of landslide, topography, soil, forest and geology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…It has also been used for quantitative evaluation in large or inaccessible areas. Logistic regression analysis has been used to evaluate ecological factors related to various topics [6,[12][13][14][15][16][17]. In related case studies, logistic regression analysis was used in various fields, such as landslide risk assessment prediction [12,14,16], wild boar habitat model development [13], amphibians habitat suitability model [6], and forest impact assessment in North Korea [5,15].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been used for quantitative evaluation in large or inaccessible areas. Logistic regression analysis has been used to evaluate ecological factors related to various topics [6,[12][13][14][15][16][17]. In related case studies, logistic regression analysis was used in various fields, such as landslide risk assessment prediction [12,14,16], wild boar habitat model development [13], amphibians habitat suitability model [6], and forest impact assessment in North Korea [5,15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Logistic regression analysis has been used to evaluate ecological factors related to various topics [6,[12][13][14][15][16][17]. In related case studies, logistic regression analysis was used in various fields, such as landslide risk assessment prediction [12,14,16], wild boar habitat model development [13], amphibians habitat suitability model [6], and forest impact assessment in North Korea [5,15]. However, as the subject of this study, there are no examples of use in the environmental evaluation of railway projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There were several studies on the comparison of different methods to obtain the best susceptibility mapping results. One of these is the work by Lee et al [4] which evaluated the probability method, logistic regression method and neural network method and concluded that probability is the most simple method and the output can be understood easily. Another work by Chuanhua and Xueping [5] analyzed the results between weight of evidence method and information method.…”
Section: Introductionmentioning
confidence: 98%
“…Worldwide, there have been many studies conducted on LSMs using different methods and models, including statistical methods using GIS [12]; LR model and probability methods [13]; the role of topography and geological structure [14]; a GIS oriented multivariate statistical assessment [15]; comparison of multivariate (logical regression) and bivariate methods using GIS procedures [16]; GIS and field survey [17]; a probability-frequency ratio model [18]; a binary logistic regression [19]; qualitative multi-criteria analysis [20]; LR versus artificial neural networks (ANN) [21]; decision tree [22]; neural network based model [23]; LR [24]; analytical hierarchy process (AHP) [25]; RF algorithm [26]; AHP, frequency ratio, and LR models [27]; frequency ratio, LR and fuzzy logic methods [10]; kernel-based Gaussian process, support vector machine (SVM), and LR [28]; a hybrid of ANN and ensemble algorithms [29]; ANFIS (adaptive neuro-fuzzy inference system), SVM, generalized additive model, and frequency ratio [30]; SVM and index of entropy models [6]; Bayes' net, radical basis function (RBF) classifier [31]; RF with the bivariate statistical method, index of entropy model, and certainty factor [32]. Recently, machine learning algorithms (MLAs) have been introduced to have better findings than conventional techniques in many areas, especially in natural hazard studies such as floods [33][34][35][36][37][38][39][40], wildfire [41], sinkholes [42], drought [43], earthquakes [44,…”
Section: Introductionmentioning
confidence: 99%